2021
DOI: 10.21037/cdt-20-1012
|View full text |Cite
|
Sign up to set email alerts
|

Non-fasting lipid profile for cardiovascular risk assessments using China ASCVD risk estimator and Europe SCORE risk charts in Chinese participants

Abstract: Background: Previous studies have shown that non-fasting lipids have similar values in cardiovascular risk estimation as fasting, but it is not clear whether this could also be applicable to Chinese participants.Methods: A total of 127 (76 men, 51 women) participants without atherosclerotic cardiovascular diseases (ASCVD) were enrolled in the study. Serum levels of blood lipids were monitored at 0 h, 2 h and 4 h after a daily breakfast. Ten-year cardiovascular disease (CVD) risk was estimated with China ASCVD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
2
0
1
Order By: Relevance
“…Varios estudios y registros poblacionales a gran escala, que incluyen niños, mujeres, hombres y pacientes con diabetes, han establecido que los lípidos plasmáticos y las lipoproteínas cambian solo modestamente en respuesta a la ingesta habitual de alimentos 30 . Las concentraciones de lípidos en periodos de no ayuna predicen un aumento del riesgo cardiovascular 31 . La mayoría de las personas comen regularmente durante el día y por lo general solo ayunan en la noche (definido como un tiempo menor de 8 horas desde la última comida), por lo que se ha planteado que una prueba de tolerancia de grasa oral es mejor para establecer las concentraciones de lípidos postprandiales 25 .…”
Section: Discussionunclassified
“…Varios estudios y registros poblacionales a gran escala, que incluyen niños, mujeres, hombres y pacientes con diabetes, han establecido que los lípidos plasmáticos y las lipoproteínas cambian solo modestamente en respuesta a la ingesta habitual de alimentos 30 . Las concentraciones de lípidos en periodos de no ayuna predicen un aumento del riesgo cardiovascular 31 . La mayoría de las personas comen regularmente durante el día y por lo general solo ayunan en la noche (definido como un tiempo menor de 8 horas desde la última comida), por lo que se ha planteado que una prueba de tolerancia de grasa oral es mejor para establecer las concentraciones de lípidos postprandiales 25 .…”
Section: Discussionunclassified
“…It is worth noting that measurement of either a fasting or non-fasting lipid profile is effective in estimating cardiovascular risk ( 39 ) and for documenting a baseline LDL-C level to evaluate cholesterol control in patients with CHD ( 40 ). In other words, the non-fasting reduction in LDL-C level either obvious or not in Chinese subjects should not be a factor interfering with the application of non-fasting blood lipid detection in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Non-fasting serum TC and TG levels were measured using a Beckman Coulter Kit (Beckman Coulter, Inc., CA, USA) since previous studies showed no significant differences between lipid profiles obtained with fasting and non-fasting blood samples. 26 - 30 …”
Section: Methodsmentioning
confidence: 99%